Pertanggungjawaban Pidana Korporasi atas Pelanggaran Hak Cipta Musik Komersial dalam KUHP 2023 - Alda Sulani; Dian Ekawaty Ismail; Ahmad (RechtJiva, 2026)
This study aims to analyze the legal status and mechanism for imposing corporate criminal liability in cases of unauthorized commercial use of music copyright under the 2023 Indonesian Penal Code (KUHP), and to examine how this general criminal law provision relates to the Copyright Law (UUHC) as a specific regulatory regime. The problem addressed is a persistent liability gap in copyright enforcement, where criminal sanctions have tended to target field-level workers while corporations, as the main economic beneficiaries (crimes for corporation), largely escape legal reach. This juridical-normative research uses a statute approach and a conceptual approach, analyzing primary and secondary legal materials through qualitative analysis with deductive-inductive reasoning. The results show that Articles 45 to 49 of the 2023 Penal Code expand the legal subject of "Any Person" to include corporate entities and open the possibility of imposing criminal liability separately or jointly on a corporation and its functional management, provided the unauthorized use of music is shown to fall within business operations, generate unlawful commercial benefit, or arise from corporate policy or omission. However, these general provisions still need to be read together with the licensing and royalty mechanisms under the Copyright Law to draw a clearer line between civil and criminal liability. This study contributes a preliminary normative framework of functional criteria for shifting liability from individual field workers to the corporation, while noting that further doctrinal and empirical inquiry is still needed to fully operationalize this model in law enforcement practice.